2022
DOI: 10.1002/htj.22661
|View full text |Cite
|
Sign up to set email alerts
|

MHD flow pattern in a parabolic mode based on the angle of inclination under cross‐diffusion

Abstract: A considerable effort has been made to draw out the flow properties of the magnetohydrodynamic fluid in parabolic movement with several parameters under cross‐diffusion. The novelty in the examination is the angle of inclination with a permeable vertical plate. The purpose of the work is to analyze the impact of some parameters on the flow in two cases, namely, obtuse angle and acute angle. The solution of the flow‐governed equations is attained by the utilization of the finite divergence technique in explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Holmedal et al 14 discussed the impact of the Soret and Dufour on an upright surface push in a porous material. Harinath Reddy et al 15,16 explained theoretically on convective fluid flow under heat growth and thermal diffusion involving MHD transfer in conducting field. Kataria and Patel 17 discussed MHD Casson fluid flow past an exponentially accelerating vertical plate, considering the effects of a chemical reaction and heat generation/absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Holmedal et al 14 discussed the impact of the Soret and Dufour on an upright surface push in a porous material. Harinath Reddy et al 15,16 explained theoretically on convective fluid flow under heat growth and thermal diffusion involving MHD transfer in conducting field. Kataria and Patel 17 discussed MHD Casson fluid flow past an exponentially accelerating vertical plate, considering the effects of a chemical reaction and heat generation/absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The study highlighted that the induced magnetic field, induced current density, and velocity are all more robust in an open‐circuit setting than in a short‐circuit arrangement. Other important research on MHD and heat transfer may be found by many authors 17–26 . To explore the performance of thermal heat generation/absorption on steady free convective flow in a coaxial porous medium, as used in petrochemical engineering, thermal process, and hydrology, Anurag et al 27 adopted Bessel functions using the variation of parameter approach to carry out this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Other important research on MHD and heat transfer may be found by many authors. [17][18][19][20][21][22][23][24][25][26] To explore the performance of thermal heat generation/absorption on steady free convective flow in a coaxial porous medium, as used in petrochemical engineering, thermal process, and hydrology, Anurag et al 27 adopted Bessel functions using the variation of parameter approach to carry out this analysis. Anurag et al 28 deliberated on the effect of Newtonian heating and cooling on laminar free convective flow in a vertical annular porosity zone, including heat generation/absorption.…”
mentioning
confidence: 99%
“…Analytical study of buoyancy effects on MHD viscoelastic fluid past an inclined plate has been discussed by Reddy et al 3 Sivaiah et al 4 investigated the study of MHD boundary layer flow of a viscoelastic and dissipative fluid past a porous plate in the presence of thermal radiation numerically. Reddy et al 5 studied the MHD flow pattern in a parabolic mode based on the angle of inclination under cross‐diffusion. Chamkha 6 discussed the non‐Darcy fully developed mixed convection in a porous medium channel with heat generation/absorption and hydromagnetic effects.…”
Section: Introductionmentioning
confidence: 99%